Elementary School Teachers' Math Teaching Efficacy Beliefs and Job Motivation: A Correlational Study - Mehdi Hosseinzadeh; S. Mahmoud Moosavinejad (University of Hormozgan, 2023)
Objective: This correlational study investigates the relationship between elementary school teachers' mathematics teaching efficacy beliefs and their job motivation in Mashhad, Iran. Methods: The research explores how teachers' confidence in their ability to teach mathematics effectively relates to their motivation to engage in their teaching profession. The participants in this study are 250 elementary school teachers from Mashhad. Data were collected through validated self-report questionnaires that assessed both mathematics teaching efficacy beliefs and job motivation. Statistical analyses, including correlation and regression, were utilized to analyze the data. Results: The results provide insights into the potential influence of teachers' self-perceived effectiveness in teaching mathematics on their overall job motivation. Conclusions: This study contributes to the understanding of the interplay between teachers' beliefs in their teaching abilities and their intrinsic motivation to excel in their profession, particularly in the context of mathematics education.